Epistemic Selectivities and the Valorisation of Nature: The Cases of the Nagoya Protocol and the Intergovernmental Science-Policy Platform for Biodiversity and Ecosystem Services (IPBES) - Ulrich Brand and Alice B.M. Vadrot (Law, Environment and Development Journal, 2013)
This article addresses the intertwined and contentious relationship between knowledge production and policy-making inside the Convention on Biological Diversity (CBD). We develop the argument that international biodiversity politics is constituted by epistemic selectivities, in which a set of favoured concepts establishes its own institutionalisation by defining ‘what needs to be governed’. Against this background the article aims to analyse the relationship between the Nagoya Protocol on Access and Benefit-Sharing and the process towards the creation of the Intergovernmental Platform for Biodiversity and Ecosystem Services (IPBES), on the one hand, and the increased popularity of the concept of ecosystem services, on the other. We argue that both cases illustrate the ‘pay to conserve logic’, prearranging the terrain of international biodiversity politics and related knowledge production and its influence on political processes. We introduce the concept of epistemic selectivities, in order to understand how this logic materialises in political institutions and to analyse the relationship between hegemonic forms of societal and scientific knowledge and that of policy knowledge. Our argument needs to be understood against the background of the wider context beyond global environmental policy by considering the political economy of biodiversity politics. This article is theoretically informed by the strategic-relational approach and focuses on the relationship between truth and power as well as on the role of the internationalised state of which the CBD is part.